Embryo Development inside Female Salamander (Ambystoma jeffersonianum-laterale) Prior to Egg Laying - Charney, Noah D. (Public Library of Science, 2014)
The length of embryo retention prior to oviposition is a critical evolutionary trait. In all oviparous salamanders, which include the vast majority of species in the order, fertilization is thought to occur at the time of egg laying. Embryos then enter the first cleavage stage several hours after being deposited. This pattern holds for previously studied individuals in the Ambystoma jeffersonianum-laterale complex. Here, we document an instance in which a female Ambystoma jeffersonianum-laterale was carrying embryos internally that had already reached stage 10 of development. Development likely began several days prior to the start of migration to the breeding pond. This is the first such record for any egg-laying salamander, and suggests a degree of plasticity in the timing of fertilization and development not previously recognized. Further work is needed to ascertain the prevalence, mechanics, and evolutionary significance of this phenomenon.